2012
DOI: 10.1098/rspb.2011.2422
|View full text |Cite
|
Sign up to set email alerts
|

Reduced metabolic rate and oxygen radicals production in stored insect sperm

Abstract: Females of internally fertilizing species can significantly extend sperm lifespan and functionality during sperm storage. The mechanisms for such delayed cellular senescence remain unknown. Here, we apply current hypotheses of cellular senescence developed for diploid cells to sperm cells, and empirically test opposing predictions on the relationship between sperm metabolic rate and oxygen radical production in an insect model, the cricket Gryllus bimaculatus. Using time-resolved microfluorimetry, we found a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
76
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(83 citation statements)
references
References 57 publications
6
76
0
1
Order By: Relevance
“…It is possible that sperm physiology is also very variable between species. An additional goal of this study was, therefore, to establish whether the relationship between sperm metabolism and oxygen radicals is similar to that observed in another insect species29.…”
mentioning
confidence: 87%
See 3 more Smart Citations
“…It is possible that sperm physiology is also very variable between species. An additional goal of this study was, therefore, to establish whether the relationship between sperm metabolism and oxygen radicals is similar to that observed in another insect species29.…”
mentioning
confidence: 87%
“…extra-sperm) interference with cell metabolic pathways in order to lower the formation of oxygen radicals in the first place. This possibility has received much less theoretical714 and empirical attention29, but may be important. A previous study found sperm metabolism in female insects was reduced over several weeks of sperm storage with the corresponding intra-sperm oxygen radicals production also being low29.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on species or lineage, sperm can be stored for days, weeks or even years making it logical to expect that spermathecae have been under selection to preserve sperm viability when that serves female fitness interests. Recent studies have indeed shown that insect females interfere with the metabolic rate of stored sperm reducing the production of harmful ROS (Reinhardt and Ribou, 2013;Ribou and Reinhardt, 2012). Another factor that affects the preservation of stored sperm is the prevalence of sexually transmitted pathogens (Knell and Webberley, 2004;Fievet et al, 2006) that might cause sperm death (Otti et al, 2013).…”
Section: Introductionmentioning
confidence: 99%